Childhood burns in Shisong, Northwestern Cameroon - Bamidele Johnson Alegbeleye (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Objective: The study aimed to highlight the pattern and treatment outcome of childhood burn injuries in northwestern Cameroon. Such reports are expected to provide preventive and improvement guidelines in our settings in the long run. Methods: Forty-two consecutive patients under fifteen with burns injuries managed at our facility were prospectively enrolled in the study. Results: The study population was 42 patients, which consisted of 23 (54%) male and 19 (46%) female, with the median 2.40±3.05 years, interquartile range of 1-14 years. The most frequent timing of burns was about mid-day (median 11:50 am). The majority of injuries were right at the patient's homes (70% cases). Interestingly, 4%, 15%, and 20% applied raw-egg, ice, and nothing as the first intervention for their children burns, respectively. Scald burns were the leading category of wounds (p<0.012). The majority of the cases were minor burns injuries with TBSA of 1-12% (p=0.002), with a mortality rate of 4%. Conclusion: Burns is still a significant health problem among children in northwestern Cameroon. Considering the application of raw egg and others like local herbs, therefore pre-hospital interventions may be harmful in our settings. Early and prompt response may be desirable, with strong advocacy for aggressive and urgent public health enlightenment campaigns on the prevention of childhood.